Energy outlooks compared: Global and regional insights - Dawud Ansari; Franziska Holz; Hashem Al-Kuhlani (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We compare prominent global energy scenarios of organisations and companies. We supplement the analysis with four own scenarios, which were derived from structured analytic techniques in combination with a numerical global energy and resource market model (Multimod). Our study provides three central contributions: (i) a compact survey of selected outlooks with meta characteristics (conceptual nature, numerical framework, qualitative elaboration) and quantitative energy system indicators at the global and regional (Europe, Asia-Pacific region, North America) level; (ii) numerous observations from a verbal analysis intended to stimulate future research; and (iii) the discussion of our own outlook. Among other conclusions, we find that scenarios essentially carrying forward current policies and/or trends lead to future worlds that do not meet the 2êC target of the Paris Agreement. Interestingly, there are both normative and exploratory scenarios reaching the Paris Agreement, and there is no consensus between outlooks on how to attain low-emission futures towards 2050. Some scenarios rely on a very strong role of renewables, others on a substantial role of negative emission technologies with fossil fuel use, yet others on assuming decreasing energy demand. There is a strong variation between outlooks with respect to transparency on scenario generation, modelling approach, and data. We argue that, in addition to transparency, the actual inclusion of a qualitative analysis of drivers and storylines helps ensure the political, social and technological feasibility of scenarios.
Keywords: Q40; Q47; Q54; C60; 330; Energy outlooks; Scenarios; Energy modelling; Climate change; Survey